Induction Chemotherapy Followed by Chemo-intensity-modulated Radiotherapy for Locally Advanced Nasopharyngeal Cancer. Issue 8 (August 2016) - Miah, A.B.; Bhide, S.A.; Del Rosario, L.; Matthews, J.; Nicol, R.; Tanay, M.A.; Gupta, S.; Zaidi, S.H.; Newbold, K.L.; Harrington, K.J.; Nutting, C.M.
Abstract: Aims: To determine the toxicity and tumour control rates after chemo-intensity-modulated radiotherapy (chemo-IMRT) for locally advanced nasopharyngeal cancers (LA-NPC). Materials and methods: Patients with LA-NPC were enrolled in a trial to receive induction chemotherapy followed by parotid-sparing chemo-IMRT. The primary site and involved nodal levels received 65 Gy in 30 fractions and at risk nodal levels received 54 Gy in 30 fractions. Incidence of ≥grade 2 subjective xerostomia was the primary end point. Secondary end points included incidences of acute and late toxicities and survival outcomes. Results: Forty-two patients with American Joint Committee on Cancer stages II (12%), III (26%) and IV (62%) (World Health Organization subtype: I [5%]; II [40%]; III [55%]) completed treatment between January 2006 and April 2010 with a median follow-up of 32 months. Incidences of ≥grade 2 acute toxicities were: dysphagia 83%; xerostomia 76%; mucositis 97%; pain 76%; fatigue 99% and ototoxicity 12%. At 12 months, ≥grade 2 subjective xerostomia was observed in 31%, ototoxicitiy in 13% and dysphagia in 4%. Two year locoregional control was 86.2% (95% confidence interval: 70.0–94.0) with 2 year progression-free survival at 78.4% (61.4–88.6) and 2 year overall survival at 85.9% (69.3–93.9). Conclusions: Chemo-IMRT for LA-NPC is feasible with good survival outcomes. At 1 year, 31% experience ≥grade 2 subjective xerostomia. Highlights: A single institution phase II study of IMRT in the treatment of NPC. Study to determine incidence of acute and late toxicities, specifically long-term xerostomia. Sequential chemotherapy/chemo-IMRT for NPC is feasible. Excellent loco-regional control and low incidence of xerostomia.